قاضی عبدالودود بحیثیت نقاد - Malik M. Tauqeer Ahmed (Tabeer e Nau, 2025)
Qazi Abdul Wadood (1896-1984) was a prestigious critic.He opted researched based critisim in Urdu. His critical reviews present thorogh critical analysis of literary researches. He remained undaunted, unbaised and rational in his writings. In critical reviews he stately showed the errors of researches besides the points. According to him , the crictic is not a teacher and critism is not the name of comprehension, elaboration, and typifying the text. Critic is stipulate to pinpoint the errors. He is deliberately responsible to show the facts without using honey tongue."Ghalib bahesiat Mohaqiq" "Azad bahesiat Mohaqiq" and "Molvi Abdul bahesiat Mohaqiq" was the pivotal series of his critical reviews. This paper introduces his critical work and also determines its worth.